Perencanaan Instalasi Pengolahan Air Minumdi Kecamatan Garut Kota, Kabupaten Garut - Indrianti Kurnia; Hartati, Etih (Jurnal Serambi Engineering, 2025)
The prolonged drought and declining water quality that struck Garut Regency in 2024 caused serious problems in the supply of clean water, exacerbated by the continuously declining water quality, thus requiring strategic steps in water resource management. This research focuses on the planning of a water treatment plant (WTP) in Garut Kota subdistrict, the area with the largest population in Garut Regency. This research aims to plan a WTP. The raw water source used is from Cimanuk River with a discharge of 313 l/second. The method used begins with an analysis of the river water characteristics based on a comparison of the river water quality with the water quality standards set by the Minister of Health Regulation No. 2 of 2023, and to determine the projection of clean water demand, a 10-year population projection is calculated. The water quality of the Cimanuk River shows that the parameters of BOD and fecal coliform exceed the standard quality standards, so a water treatment process with a series of units is needed, starting from the raw water intake, through coagulation, flocculation, sedimentation, filtration, to the final stage of disinfection. The maximum water demand is 164 l/s in 2034. The treatment results include BOD of 1.59 mg/L and Fecal Coliform of 0.0178 CFU/100ml; these values indicate that the treatment results meet the quality standards.